Assessment of Free Radical Scavenging Potency and In-vitro Antioxidant Analysis of Ximenia caffra (Sour Plum) Leaf - Jacob A.D.; Dauda J.A.; Daniel O.A; Nayo R.O.; Maji D.C.; Umar I.; Wada H.A. (Covenant Journal of Physical and Life Sciences, 2021)
This study is focused on the determination of the free radical scavenging potency and in-vitro antioxidant analysis of extracts of Ximenia Caffra (sour plum) leaf, (using methanol, chloroform and n-hexane as solvent. About 50.0g of the powdered samples was weighed into a beaker and methanol (300 mL) was added into it. The same process was repeated for chloroform and n-hexane extract. The DPPH free radical scavenging assay were carried out using ascorbic acid as the positive control. The results of the analysis at 50, 100, 200, 400 and 800 μg/mL shows the following % inhibition: (40, 50, 65, 80, and 91), for the methanolic extract, (16, 18, 26, 29, and 33), for the chloroform extract and (13, 17, 21, 32, and 55), for the n-hexane extract. The IC50 (µg/mL) values revealed 71.83 for the methanol extract, 1500 for the chloroform extract, and 715.05 for the n-hexane extract. From the result, it can be concluded that sour plum leaves can be used in the treatment of certain diseases such as diabetes, hypercholesterolemia, insomnia, and liver problems in which the participation of reactive oxygen species have been implicated.